Climate-induced growth responses and tree-line shifts of boreal conifers in the alpine and polar tree-line ecotone in Finnish Lapland - Franke, Anna Katharina (2020)
At the northern margins of the boreal regions bordering the sub-Arctic, trees as a life form grow close to the limit of their ecological range and have to cope with low temperatures, low nutrient supply, and sparse light conditions during winter. The growing season lasts less than five months during which trees need to pass through all vegetative and reproductive stages. In the transition zone from closed forests to bare fell tops and open tundra, conifers form the outermost edge of their distribution area in the tree-line ecotone, which is characterized by harsh climatic conditions and disturbance regimes, challenging tree growth by frost, wind and snow load. The mortality rate is high and sequences of several favourable years are needed to grow and successfully establish sustainably high seed crops for natural regeneration. Here, temperature is found to be the limiting parameter for growth and regeneration, hence a temperature rise under current warming is expected to considerably improve the growing conditions for conifers (Kauppi et al. 2014; Salminen and Jalkanen 2015). Under mild winters, early springs and increasing summer temperatures, trees and shrubs are predicted to establish more successfully, regionally replacing graminoids in the alpine oroarctic tundra by higher vegetation (Juntunen et al. 2002; Jia et al. 2003; Goetz et al. 2011; Jeong et al. 2012; Walker et al. 2012; Pearson et al. 2013; Aakala et al. 2014). An expansion of conifers beyond the recent tree-line position may affect the microclimate and carbon fluxes of the ecosystem, potentially influencing large-scale circulation changes in Arctic regions (Jeong et al. 2012; Miller and Smith 2012; Pearson et al. 2013; Zhang et al. 2013). Estimating vegetation shifts in these regions is consequently of high scientific interest and is also in the focus of the present project. In Finnish Lapland, a monitoring project was established already in 1983 to monitor regeneration and growth of Scots pine (Pinus sylvestris L.) and Norway spruce (Picea abies ...